The Development of Chemistry E-Module Using STS Approach Based on HOTS on Acid-Base Materials - Syauqi, Salma; Suyanti, Retno Dwi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aimed to develop a chemistry e-module using the Science Technology Society (STS) approach based on Higher Order Thinking Skills (HOTS) on acid-base materials for Grade XI students at SMA Negeri 2 Medan. The research employed the 4D development model (Define, Design, Develop, Disseminate). The Define stage identified that chemistry learning—particularly on acid-base topics—was still dominated by conventional methods with limited digital media. The Design stage produced an e-module named KelasKimia.ku, published via Google Sites. In the Develop stage, expert validation was conducted by three validators: content expert (mean score 3.50; Very Feasible), media expert (mean score 3.20; Feasible), and learning expert (mean score 3.30; Feasible). The Disseminate stage involved 71 students across two Grade XI classes. Student response yielded a mean score of 3.60 (Very Feasible). Learning outcomes showed that the experimental class (using the STS-HOTS e-module) achieved a posttest mean of 85.86, compared to 81.39 in the control class. The experimental class obtained an N-Gain of 0.7734 (High category), significantly higher than the control class (0.6971; Moderate). Paired Samples t-Test results showed t = −32.300 with significance 0.000 (< 0.05), confirming that the e-module effectively improved students’ HOTS and learning outcomes on acid-base materials.